1997
DOI: 10.1038/40187
|View full text |Cite
|
Sign up to set email alerts
|

Calcium sensitization of smooth muscle mediated by a Rho-associated protein kinase in hypertension

Abstract: Abnormal smooth-muscle contractility may be a major cause of disease states such as hypertension, and a smooth-muscle relaxant that modulates this process would be useful therapeutically. Smooth-muscle contraction is regulated by the cytosolic Ca2+ concentration and by the Ca2+ sensitivity of myofilaments: the former activates myosin light-chain kinase and the latter is achieved partly by inhibition of myosin phosphatase. The small GTPase Rho and its target, Rho-associated kinase, participate in this latter me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

136
2,365
10
16

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,707 publications
(2,527 citation statements)
references
References 28 publications
136
2,365
10
16
Order By: Relevance
“…We observed a rapid concentration-dependent decrease of PO 4 -MLC2 in response to SB-431542 in REF52 cells (Figure 1d). Inhibition of PO 4 -MLC2 levels was readily observable with 5 mM SB-431542 treatment, and this further declined with 10 and 20 mM SB-431542 treatments and approached the level of inhibition reached after treatment with the ROCK inhibitor Y27632 (Uehata et al, 1997) (Figure 1d). …”
Section: Rapid Activation Of Rhoa By Tgf-b Is Blocked By the Alk5 Kinmentioning
confidence: 83%
“…We observed a rapid concentration-dependent decrease of PO 4 -MLC2 in response to SB-431542 in REF52 cells (Figure 1d). Inhibition of PO 4 -MLC2 levels was readily observable with 5 mM SB-431542 treatment, and this further declined with 10 and 20 mM SB-431542 treatments and approached the level of inhibition reached after treatment with the ROCK inhibitor Y27632 (Uehata et al, 1997) (Figure 1d). …”
Section: Rapid Activation Of Rhoa By Tgf-b Is Blocked By the Alk5 Kinmentioning
confidence: 83%
“…Thus, U2OS cells were treated with 1530 distinct chemicals from the ICCB Known Bioactives Library or the US-Drug Collection (encompassing most US Food and Drug Administration-approved and some experimental drugs), alone or in combination with MTX, for 18 h, stained with quinacrine and then analyzed by automated, quantitative epifluorescence microscopy ( Figure 2a). This screen led to the identification of several compounds that are capable of preventing the MTX-triggered loss of quinacrine-dependent fluorescence (Figure 2b): monensin, which blocks intracellular trafficking and exocytosis; 38 blebbistatin, which inhibits myosin II, thereby blocking the apoptosis-associated blebbing of the plasma membrane; 39 Y-27632, which inhibits ROCK1, 40 a protein that -upon cleavage by caspase-3 -participates in apoptotic blebbing; 41,42 and mefloquine, which inhibits PANX1 channels. 43 Subsequent validation experiments confirmed that monensin, blebbistatin and several chemically-unrelated inhibitors of ROCK1 (i.e., Y-27632, bearing with a central aminoethyl group, and H-1152, characterized by a central sulfonyl junction) and PANX1 (i.e., the synthetic quinine analogue mefloquine and the disulfonic stilbene derivatives 4,4 0 -diisothiocyano-2,2 0 -stilbenedisulfonic acid (DIDS) and 4-acetamido-4-isothiocyano-stilbene-2,2-disulfonic acid (SITS)) blunt the loss of quinacrine fluorescence as triggered in U2OS cells by MTX (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…The Rho-associated coiled-coil forming protein kinases p160ROCK/ROCK-1 (Ishizaki et al, 1996 and ROCK-a/ROCK-2 (Leung et al, 1996;Matsui et al, 1996) are direct downstream effectors of RhoA that regulate actin stress fiber formation. They are specifically inhibited by the synthetic pyridine derivative, Y-27632 (Uehata et al, 1997;Ishizaki et al, 2000). Pretreatment of PC-3 cells for 60 min with 10 mM Y-27632 abolished actin stress fiber formation stimulated by bombesin (panel d)) and ET-1 (panel f), demonstrating that bombesin and ET-1 stimulate the RhoA effector, ROCK, to direct cytoskeletal reorganization.…”
Section: Resultsmentioning
confidence: 99%